Beetlejuice [videorecording (Blu-Ray)] - Baldwin, Alec; Davis, Geena; Keaton, Michael, 1951-; Burton, Tim, 1958- (Warner Home Video, 2008)
A recently deceased Connecticut couple decide to use the maniacal bio-exorcist Betelgeuse to help rid them of the trendy New Yorkers who have moved into their home.